PEMANFAATAN LIMBAH CAIR TAHU SEBAGAI PROBIOTIK BUDIDAYA PERIKANAN - Mohammad Mirwan; Mila Shintya Rahmansari (EnviroUS, 2022)
Tofu liquid waste contains organic elements that contain nutrients such as protein, fat, and good bacteria. The purpose of this study was to determine the potential utilization of tofu liquid waste as a probiotic and to determine the optimum ratio of tofu wastewater use as a probiotic. The method used is fermentation and adding ingredients that contain nutrients and good bacteria (Lactobacillus sp.). Analysis of the data to determine the quality of probiotics using the abundance test of Lactobacillus sp. and proximate analysis which includes protein content, fat content, ash content, and water content then the results are compared with the quality standard of commercial probiotics. The best combination of probiotics is V2 = Variable 2 (Waste ciar tofu 50%, Molasses 23%, Coconut water 20%, Yeast Tape 5%, Yakult 2%) with the results of the analysis of the abundance of Lactobacillus sp. of 105 CFU/ml and the results of the analysis of the proximate test of protein content parameters of 2.9%; fat content of 0.93%. In this case, the results of the V2 test still have 3 nutritional contents that have met the quality standards of commercial probiotics.